A STUDY ON INDONESIAN-ENGLISH CODE MIXING USED IN PC PLUS MAGAZINE - ISMAWATI , ARIFATUL (2007)
This research paper is aimed at answering the three problems. The problems are: (1) the form of code mixing used in PC PLUS magazine, (2) the referential meaning of code mixing used in PC PLUS magazine, and (3) the reason of using code mixing in PC PLUS magazine. This research uses documentation methods to get the data. The data are the English words in PC PLUS magazine, in the form of words and phrases. The sources of data are PC PLUS magazine edition 237 August 2005, 277 February 2007, 285 June 2007, 287 July 2007 especially in column trick, actual, tutorial, and focus. To answer those problems, this research employs morphological and syntactical form of code mixing. To find out the meaning of those code mixings this research use referential meaning, and the reason of using code mixing use Ohoiwutun's theory that breaks those reason into need filling motive and prestige filling motives. The result of this study shows that first, there are 57 data of morphological form that breaks into 25 data of word, 5 data of verb, 1 data of adjective, 2 data of reduplication, 17 data of compounding, 7 data of hybrid and 18 data of syntactical form that breaks into 13 data of noun phrase, 3 data of verb phrase, and 1 data of adjective phrase. Second, the meaning of each word is using referential meaning. Third, the reason of using code mixing is need filling motive.